2017
DOI: 10.1088/1612-202x/aa548f
|View full text |Cite
|
Sign up to set email alerts
|

A 400 Gbps/100 m free-space optical link

Abstract: A 400 Gbps/100 m free-space optical (FSO) link with dense-wavelength-division-multiplexing (DWDM)/space-division-multiplexing (SDM) techniques and a doublet lens scheme is proposed. To the best of our knowledge, this is the first time that a link adopting DWDM and SDM techniques and a doublet lens scheme has demonstrated a 400 Gbps/100 m FSO link. The experimental results show that the free-space transmission rate is significantly enhanced by the DWDM and SDM techniques, and the free-space transmission distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…A DWDM-FSO communication system that uses a multi-beam with the space division multiplexing (SDM) technique [15] can be a succedaneum for the proposed WDM-FSO communication system, which transmits hybrid signals through the doublet lens scheme (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A DWDM-FSO communication system that uses a multi-beam with the space division multiplexing (SDM) technique [15] can be a succedaneum for the proposed WDM-FSO communication system, which transmits hybrid signals through the doublet lens scheme (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the WDM channels that are modulated with different signals are proposed by using only simulated results [10]- [14]. The optical lens for the multi-beam WDM-FSO increase with the number of WDM channels, thereby considerably increasing the cost of the network [6]- [9], [15]- [17]. This study demonstrates a WDM-FSO communication system that transmits hybrid signals, wherein four wavelengths are modulated with various high-speed signals using a single beam.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note the contrast with free-space optical (FSO) networking, another feasible approach to achieving wireless links with Tb/s throughput. FSO links can also employ frequency multiplexing, and like a THz link, the signals propagate as directional beams, not omnidirectional broadcasts 41 . However, the wavelength-dependent diffraction effects described here would not be expected to manifest themselves in FSO systems.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant parameter here, to determine the significance of diffraction effects, is the spacing between adjacent frequency channels d v , as a fraction of the average carrier frequency v 0 . In a typical frequency-multiplexed FSO system 41 , this fractional spacing d v / v 0 is quite small, on the order of 10 −4 . In contrast, for our system demonstration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, doublet lenses can be adopted as a substitute for afocal telescopes to reduce the divergence of laser beam and extend the free-space transmission distance. Other previous study demonstrated a 400 Gbps/100 m FSO link with dense-wavelength-division-multiplexing (DWDM) and space-division-multiplexing (SDM) schemes [7]. A 16-parallel 25-Gbps FSO link with an overall data rate of 400 Gbps over a 100-m free-space transmission is illustrated.…”
Section: Introductionmentioning
confidence: 92%